Pathology of fatal Baylisascaris schroederi infection in a wild giant panda - Chang Lingling; Zhang Danhui; Wang Yashi; Ren Zun; Wu Yaping; Zhang Qiang; Zhao Guanghui; Pan Guanglin; Wang Xinglong; Zhao Xiaomin; Tong Dewen (Parasite, 2025)
Baylisascaris schroederi McIntosh, 1939 (Ascarididae), a nematode specific to giant pandas (Ailuropoda melanoleuca), is a major health threat, particularly to wild populations. A 20-year-old wild adult female giant panda rescued from a Chinese nature reserve died with a 2-month history of emaciation and weakness. Necropsy was performed. Grossly, the giant panda was very thin with minimal fat stores throughout, and marked serous atrophy of fat around the kidneys. Mesenteric edema was very pronounced in the posterior intestine. The abdominal cavity contained approximately 5 L of orange-yellow, translucent, low-viscosity fluid. There were ca. 1,660 robust ascarids occupying the lumen of the esophagus, stomach, and intestines. Microscopically, the intestine showed moderate necrotizing and eosinophilic enteritis with adult nematodes, consistent with an ascarid. PCR and sequencing confirmed that the ascarid species was B. schroederi. This case highlights a fatal B. schroederi infection in a wild giant panda, with malnutrition and possible multiple organ failure identified as the primary causes of death.